Knowledge Level of Pregnant Women in Cipacing Village on Nutrition and Benefits of Colostrums - Reddy, Haviz; Fatimah, Siti Nur; Zulvayanti, Zulvayanti (Althea Medical Journal, 2015)
Â Â Â Background: Colostrums are the only natural food that is healthy for newborn infants since colostrums contain proper nutrition needed for infantsâ growth. This study aimed to reveal the knowledge level of pregnant women on nutrition and benefits of colostrums.Â Methods: This study used descriptive cross-sectional method on 73 pregnant women in Cipacing village, Jatinangor district, Sumedang Regency, West Java, from October 18 to November 14, 2012. A questionnaire was used.Â Results: The results showed that the characteristics of these pregnant women were as follows: 20-35 years old (53.4%), most were middle school graduates (42.5%), most were unemployed (72.6%), and some claimed to have never given birth before (37,0%). Mostly, the knowledge level of these pregnant women was in the category of âfavorableâ (84.9 %). The knowledge level with the highest percentage (100%) came from pregnant women aged above 35 years old, college graduates, employed as private employees, civil servants, or self-employed, as well as having three biological children or more.Â Conclusions: Sustained health promotion and counseling programs are needed to maintain already-favorable knowledge level; thus pregnant womenâs knowledge on nutrition and benefits of colostrums can be applied and can also encourage these women themselves to provide colostrums for their newborn infants.Keywords: Benefits of colostrums, Jatinangor, nutrition, womenâs knowledge levelÂ Â Â Â DOI: 10.15850/amj.v2n1.422Â